ESTRUTURA AGRÁRIA E IRRIGAÇÃO NO NORDESTE* - teoora, José Graziano da Silva; Kageyama, Angela; Buainain, Antonio Márcio; Revdon, Bastuaan P.; Silveira, Jose Maria J.; Pinto, Luis Carlos Guedes; Mello, M. Tereza L.; Bıral, Mario A. M.; Porto, Mavla Y.; lemos, Paulo B.; Ramos, Pedro; Fonseca, Rinaldo B.; et al. (Revista Econômica do Nordeste, 1989)
Acervo Historico